Users Acceptance and Sense of Presence towards VR Application with Stimulus Effectors on a Stationary Bicycle for Physical Training - Mahalil I.B.; Yusof A.B.M.; Ibrahim N.B.; Mahidin E.M.B.M.; Hwa N.H. (Science and Information Organization, 2023)
Audition; Surveys; Wind effects; Wind power; 'current; Computer generated; Immersive; Physical training; Pilot studies; Sense of presences; Stimulus effector; Technology acceptance; Users' acceptance; Virtual reality technology; Virtual reality